Capitals of capital a history of international financial centres, 1780-2005 - Cassis, Youssef (Cambridge University Press, 2006)
International financial centres have come to represent a major economic stake, yet no historical study has been devoted to them. Professor Cassis, a leading financial historian, attempts to fill this gap by providing a comparative history of the most important centres that constitute the capitals of capital.